2013
DOI: 10.1121/1.4811159
|View full text |Cite
|
Sign up to set email alerts
|

The roles of fundamental frequency contours and sentence context in Mandarin Chinese speech intelligibility

Abstract: Flattening the fundamental frequency (F0) contours of Mandarin Chinese sentences reduces their intelligibility in noise but not in quiet. It is unclear, however, how the absence of primary acoustic cue for lexical tones might be compensated with the top-down information of sentence context. In this study, speech intelligibility was evaluated when participants listened to sentences and word lists with or without F0 variations in quiet and noise. The results showed that sentence context partially explained the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
41
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 14 publications
(23 reference statements)
8
41
2
Order By: Relevance
“…Chen et al [7] showed that, although tone contours were not important in sentence perception in quiet, their importance increased in noise. Wang et al [10] and Xu et al [11] reported similar findings.…”
supporting
confidence: 52%
“…Chen et al [7] showed that, although tone contours were not important in sentence perception in quiet, their importance increased in noise. Wang et al [10] and Xu et al [11] reported similar findings.…”
supporting
confidence: 52%
“…2. The findings in this study are consistent with results from previous work (e.g., Chen et al, 2014;Wang et al, 2013). Early work showed that while the F0-contour information was important for Mandarin sentence perception, its perceptual contribution could be compensated by other cues (e.g., context information) in quiet.…”
Section: Discussionsupporting
confidence: 92%
“…F0 contour carries the most distinctive information for lexical tone identification, and temporal envelope and duration are secondary cues contributing to lexical tone recognition (e.g., Fu et al, 1998). The importance of lexical tone contour for Mandarin sentence perception has been noted in various studies (e.g., Chen et al, 2014;Wang et al, 2013). For normal-hearing (NH) listeners, while lexical tone contours do not influence sentence understanding in quiet, they significantly impact Mandarin sentence intelligibility in noise (e.g., Chen et al, 2014;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Speech recognition accuracy was determined by a keyword-correct count where each content word provided a potential key word (Scott et al, 2004;Wang et al, 2013). Percent-correct score was obtained based on the number of correct responses (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the significant interaction between F 0 contours and listening condition revealed that natural F 0 contours provided extra benefit in the interference condition, whereas the absence of interaction effect between semantic context and listening condition showed that semantic context contributed to speech recognition to a similar degree in both the quiet and interfering backgrounds. In a tonal language like Mandarin Chinese, F 0 contours play an important role in speech recognition, especially when speech is presented without contextual information (e.g., isolated syllables) or in adverse listening conditions (e.g., in the presence of N-talker babbles) (Patel et al, 2010;Wang et al, 2013;Yang et al, 2015). The significant main effect of F 0 contours and interaction effects between F 0 contours and listening condition/semantic context indicate that older listeners have the ability to use F 0 information to assist speech recognition, especially in the presence of interfering speech or absence of sentential semantic context.…”
Section: Discussionmentioning
confidence: 99%